Tektonika střední části Moravského krasu - Tóthová, Gabriela (2011)
This work is focused on study of tectonic structure of the central part of Moravian carst. The main theme is to reassume to know structure of northern and southern part of Moravian carst. Own and recieved data like orientation of tectonic structures (bedding, fold axe etc.) was used for evolement of this work. The measured data were worked up by Spheristat software, where were done contour diagrams and maps of trends. It was discovered, that in studied area took place various phases of deformation. There is a few generations of thrusts that are complicating the whole structure. Older variscan thrust are deformed by younger variscan trhusts. Original fold are re-folded and fold axes are curved. This structure is deformated by alpinian tectonics.